Corporate Tax Integrity and the Cost of Debt: Evidence from China. Issue 6 (3rd May 2022) - Wang, Pin; Zhou, Ali; Wang, Yi
ABSTRACT: This study examines whether and how tax integrity affects the cost of debt. Whereas most previous studies capture firms' trust indirectly, we capture a firm's earned trust more directly by using its tax-paying credit rating as a proxy. We find that tax integrity is negatively related to the cost of debt. We also examine whether the firm ownership affects the relationship between a firm's tax integrity and the cost of debt, and find a negative effect that is only significant for non-state-owned enterprises. Finally, we identify business risk as a channel through which tax integrity affects the cost of debt.